Apakah Yang Memengaruhi Kesadaran Mahasiswa Atas Pajak? - Astri Nur Komala; Trismayarni Elen (Jurnal Ilmiah Akuntansi Universitas Pamulang, 2021)
The objective of study is to analyze affect of tax education, tax training and tax assessment on student awareness of tax. The research sample are 101 respondents who were active students in the Tax Center with accidental sampling techniques in several universities in Jakarta area. Multiple regression was used to test hypothesis to analyze affect of factors that student awereness of tax. The result of this study shows that there has no a positive and not significant effect on tax education, but there has a positive and significant effect on tax training and tax assesment on student awareness of tax.